Analysis of Factors Influencing the Interest of Class XII Accounting Students of SMK NU Gresik to Continue Their Education to Higher Education - Ananda Putri Nabilah; Agung Listiadi (Journal of Innovative and Creativity, 2025)
Higher education is a key pillar in improving the quality of human resources in today's era of globalization and free competition. However, the participation rate of vocational high school (SMK) students, particularly those majoring in accounting, in continuing their education to higher education remains relatively low. This situation also occurs at SMK NU Gresik, where most graduates choose to go directly to work rather than continue their studies. This study aims to empirically analyze the factors influencing the interest of 12th-grade Accounting students at SMK NU Gresik in continuing their education to higher education. Seven independent variables were examined in this study: learning motivation, perceptions of higher education, academic self-confidence, parental support, family economic situation, peer influence, and the role of schools/teachers. The method used was an associative quantitative approach using a survey technique. Sampling was conducted using simple random sampling, with 114 respondents from a total population of 159 12th-grade Accounting students. The research instrument was a closed-ended questionnaire using a five-point Likert scale. Data analysis was performed using multiple linear regression to test the simultaneous and partial effects of each variable on interest in continuing higher education. The results of the study indicate that all seven independent variables simultaneously significantly influence student interest. Partially, learning motivation, perceptions of higher education, academic self-confidence, and parental support have a significant influence, with learning motivation and parental support being the dominant factors. Meanwhile, family economic conditions, peer influence, and the role of the school have insignificant influences in the partial regression model, although they remain contextually relevant in students' educational decisions. These findings have important implications for schools, guidance and counseling (BK) teachers, and parents in creating an educational ecosystem that encourages vocational high school students, particularly those majoring in accounting, to pursue higher education. Strategic interventions are needed to increase learning motivation through academic mentoring programs, the provision of scholarship information, and the active involvement of parents and teachers in students' educational decision-making processes. This study also makes a theoretical contribution to the vocational education literature by demonstrating that success in further education is not solely determined by external conditions such as economics, but is also strongly influenced by psychological and social factors inherent in the students themselves.